Assay of miRNA in cell samples using enhanced resonance light scattering technique based on self aggregation of magnetic nanoparticles. (2nd October 2018) - Yue, Qiaoli; Tao, Lixia; Hou, Yining; Zhang, Cong; Wang, Yongping; Hong, Min; Li, Chen-Zhong
Aims: miRNAs are regarded as potential biomarkers correlated with the development and progression of many diseases. However, it is a challenge to construct a sensitive method to detect them without using time-consuming radioactive labeling or complex amplification strategies.Methods: A facile resonance light scattering (RLS) system was developed for the detection of miRNA employing magnetic nanoparticles (MNPs) as RLS probes. MNPs were coated with streptavidin. DNA probes were modified on the surface of MNPs based on the specific interaction of streptavidin and biotin forming MNPs@DNA probes. MNPs@DNA probes dispersed in homogeneous media causing low RLS signal.Results & conclusion: miRNA hybridized with DNA probes resulting in the aggregation of MNPs and inducing the enhancement of RLS intensity. miRNAs were determined successfully with limit of detection at 0.9 picomole per liter (pM). The potential clinical application of the present biosensor was also demonstrated by measuring miRNAs in human normal and cancer cells, and human serum samples.